Insulin‐like growth factor 1 improves neurobehavior in hemisected spinal cord injury but is not associated with BDNF signal. Issue 2 (28th June 2019) - Zhong, Zhan‐Qiong; Zou, Yu; Cheng, Jian‐Min; Liang, Nan; Xia, Qing‐Jie; Zhang, Xiao
Abstract : Background: Spinal cord injury (SCI) is concomitant with serve dysfunction, without effective treatment. In this study, we investigated the role of insulin‐like growth factor 1 (IGF‐1) and associated signal in hemisected spinal cord. Methods: Rats were subjected to spinal cord hemisected injury and were evaluated by behavioral tests. The expression of IGF‐1 was determined by using immunohistochemistry, quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot to examine the role of IGF‐1 in the hemisected spinal cord. Results: Basso, Beattie and Bresnahan (BBB) scores exhibited an immediate decrease in rats after spinal cord hemisection, which was followed by an increase at the later stage of injury. In corresponding to behavioral change, the expression of IGF‐1 was significantly down‐regulated after injury. Moreover, the IGF‐1 knockdown mouse was applied for detecting the role of IGF‐1. After hemisected spinal cord injury (hSCI), decreased BBB and Basso Mouse Scale (BMS) scores appeared in the injured side, which supported that IGF‐1 could play a crucial role in neuro repair. Subsequently, the mechanism of IGF‐1 for neuroplasticity was explored in cultured neurons subjected to IGF‐1 overexpression together with down‐regulating brain‐derived neurotrophic factor (BDNF), and the results showed that BDNF administration failed to influence the consequence of IGF‐1 overexpression in neurons, suggesting BDNF is not the mechanism of the IGF in SCI repair. Conclusion: IGF‐1 regulated neuroplasticity in the hemisected spinal cord, which was not associated with BDNF expression.